Biomechanical evaluation of movement in sport and exercise the British Association of Sport and Exercise Sciences guide - Payton, Carl; Burden, Adrian (Routledge, Taylor & Francis Group, 2018)
Now in a fully updated and revised new edition, this is still the only up-to-date, practical guide to the use of technology in sport and exercise biomechanics. It includes detailed explanations of the key theory underlying biomechanics testing and measurement, along with advice on choosing equipment and using it effectively.